Interfrontal Bone Among Inbred Strains of Mice and QTL Mapping - Zimmerman, Heather; Yin, Zhaoyu; Zou, Fei; Everett, Eric T. (Frontiers in Genetics, 2019)
The interfrontal bone (IF) is a minor skeletal trait residing between the frontal bones. IF is considered a quasi-continuous trait. Geenetic and environmental factors play roles in its development. The mechanism(s) underlying IF bone development are poorly understood and may involve de novo secondary ossification centers, induction by the interfrontal suture or underlying dura. We sought to survey inbred strains of mice for the prevalence of IF and to perform QTL mapping studies. Archived mouse skulls from a Mouse Phenome Project (MPP) were available for this study. 27 inbred strains were investigated (129S1/SvImJ, A/J, AKR/J, BALB/cByJ, C3H/HeJ, C57BL/10J, C57BL/6J, C57/LJ, C58/J, CAST/Ei, CBA/J, DBA/1J, DBA/2J, DBA/LacJ, FVB/NJ, LP/J, MOLF/EiJ, NOD/LtJ, NZB/B1NJ, NZW/LacJ, PERA/EiJ, PL/J, SJL/J, SM/J, SPRET/Ei, SWR/J, WSB/Ei) with 6-20 mice examined for each strain. Skulls were viewed dorsally and the IF measured using a zoom stereomicroscope equipped with a calibrated reticle. A two generation cross between C3H/HeJ and C57BL/6J mice was performed to generate a panel of 468 F2 mice. F2 mice were phenotyped for presence or absence of IF bone and among mice with the IF bone maximum widths and lengths were measured. F2 mice were genotyped for 573 SNP markers were informative between the two strains and subjected to linkage map construction and interval QTL mapping. Results: Strain dependent differences in the prevalence of IF bones were observed. Overall, 77.8% or 21/27, of the inbred strains examined had IF bones. Six strains of mice (C3H/HeJ, MOLF/EiJ, NZW/LacJ, SPRET/EiJ, SWR/J, and WSB/EiJ) lack IF bones. Among the strains with IF bones, the prevalence ranged from 100% for strains such as C57BL/6J, C57/LJ, CBA/J, NZB/B1NJ down to 5% for strains such as CAST/Ei. Six of the 27 inbred strains lacked IF. QTL mapping for IF bone length and widths identifies for each trait one strong QTL detected on chromosome 14 along with several other significant QTLs on chromosomes 3, 4, 7 and 11. Strain dependent differences in IF will facilitate investigation of genetic and environmental factors contributing to IF development. IF bone formation may be a model to understand wormian bone formation.